The Power of Excess: Royal Incest and the Ptolemaic Dynasty - Ager, Sheila L. (Anthropologica, 2022)
The Greco-Macedonian dynasty of the Ptolemies, which ruled Egypt from 322 until 30 BCE, established early on a practice of incestuous marriage in the royal house. This custom, which may have had a number of pragmatic functional purposes, was on a more profound level symbolic of royal power. But royal incest, as practised by the Ptolemies, was only one of a larger set of behaviours, all of which were symbolic of power, and all of which were characterized by lavishness, immoderation, excess and the breaching of limits in general.